MULTIPLICATION AND DIVISION (MnD) BOARD MEDIADEVELOPMENT TO INCREASE THE MULTIPLICATION AND DIVISIONCALCULATION ABILITY OF CLASS III ELEMENTARY SCHOOL STUDENTS - Dewa Ayu Made Manu Okta Priantini; Dewa Made Dwicky Putra Nugraha; Ni Gusti Agung Ayu Sinta Dewi (International Conference on Multidisciplinary Research Perspective, 2025)
This study aims to produce learning media in the form of Multiplication And Division (MnD) boards to improve the ability to calculate multiplication and division of third grade students of SD Negeri 6 Sumerta which is feasible to be applied in classroom learning. This research was a development research using the ADDIE model which consists of five stages namely analysis, design, development, implementation, and evaluation. The research subjects consisted of 2 media experts, 2 material experts, and users consisting of 34 students and 2 teachers. While the object of this research included the validity of Multiplication and Division (MnD) board media to improve the ability to calculate multiplication and division of mathematics. The data collection instruments used were media and material validation sheets, media practicality questionnaires, and multiplication and division tests. The research data were analyzed using quantitative descriptive analysis techniques. The results showed that the media validity test got a result of 0.86 with very high criteria, then the results of the material validity test got a result of 1.00 with valid criteria, the results of the practicality test got an average score of 92.5% with very practical criteria, then the results of the effectiveness test in the form of student calculation ability scores of 91.24 with very good criteria. The conclusion of this study was that the Multiplication And Division (MnD) board media developed has met the criteria for feasibility for use in learning mathematics and was effective in improving the ability to calculate multiplication and division of third grade students of SD Negeri 6 Sumerta.